Science learning module based on local potential of Grenden village on digestive system material to improve problem solving ability of junior high school students - Sri Wahyuni; Jensi Arista; Ulin Nuha; Julia Astutik (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Problem-solving ability is a fundamental skill that students must develop in science education. However, many students continue to face challenges in mastering this competence. This study aims to develop a valid, practical, and effective science learning module to enhance students' problem-solving skills. The research adopts a Research and Development (R&D) approach using the ADDIE development model. The study was conducted at SMP Sultan Agung Puger during the odd semester of the 2024/2025 academic year, involving 22 students as research participants. The findings indicate that the developed science learning module meets the criteria for validity, practicality, and effectiveness. The validity assessment yielded an average score of 82.12%, indicating a high level of validity. The practicality evaluation of the module’s implementation in science learning resulted in an average score of 85.13%, demonstrating strong practical applicability. The module’s effectiveness, assessed through pre-test and post-test analyses, showed an N-gain score of 0.63, classified as a medium improvement. Additionally, student responses to the module's implementation received an average score of 87.72, categorized as very good. In conclusion, the Science Learning Module Based on the Local Potential of Grenden Village meets the criteria of validity, practicality, and effectiveness in enhancing students’ problem-solving skills. These findings suggest that integrating localized content into science education can improve student engagement and learning outcomes.